Quality Aspects of Dried Fish Marketed in the North Eastern States of India - P.K., Vijayan; P.K., Surendran (Fishery Technology, 2025)
Physical, sensory, biochemical and microbiological quality of dry fish products (nine unsalted and six salted) available in Jagi Road dry fish market of Assam was evaluated. Moisture content varied from 11.08 to 44.32% and salt content from 0.26 to 3.4% in unsalted and from 15.71 to 52.76% in salted samples. Ash content varied from 9.28 to 28.72% in different samples. The TVBN value was in the range of 205 to 427 mg% in eight samples while in seven samples, it was from 49 to 186 mg%. Escherichia coli was absent in all the samples, while coagulase positive staphylococci was present in one sample and faecal streptococci in two samples. Fungi was present in all the samples except one. The study showed that 80% of the products traded were of poor quality.